Determinants of road traffic accidents cases in tertiary care hospital at Ranchi, Jharkhand - Kujur, Manisha; Kiran, Asha; Xaxa, Anuj Pankaj; Kashyap, Vivek (International Journal Of Community Medicine And Public Health, 2019)
Background: Worldwide, road traffic accident (RTA) poses a public health and development challenge and greatly affects the human capital development of every nation. This study aims in providing tangible evidences about determinants of road traffic accident cases at tertiary care center with a good area coverage giving insight into burden of RTA. Methods: This study was cross sectional hospital based study done in Rajendra Institute of Medical Science Ranchi, Jharkhand. Patients coming to emergency department were recorded and followed in ENT, neurosurgery and orthopedics department of RIMS, Ranchi in the period of one month (15th January to 20th Febuary2019). Results: Most of the patients were (59%) among the age group of 19-35 years of which 89.5% of the patients were male. 84.8% of the accident took place while motorcycle was driven. 53.3% of the patients were without license. Majority of the cases were driving between the speed of 30-60 km/hr at the time of accident. Majority of cases were not wearing helmet at time of accident (76%). Majority of accidents took place in state highway (53.3%) (roads connecting major cities of states). 59% of the accident took place at T-type junction. Major factor responsible was unusual behavior of man and animal (19%) and followed by overtaking (18.1%). Majority of the accidents were due to front collision (34.3%). Conclusions: There is a need for encouraging and promoting safe driving behavior among community members by the awareness through road safety campaigns and enforcement of road traffic laws to bring down the burden of RTA.